The gold(I)-mediated domino reaction to fused diphenyl phosphoniumfluorenes: Mechanistic Consequences for Gold-Catalyzed Hydroarylations and Application in Solar Cells - Arndt, Sebastian; Antoni, Patrick W.; Rominger, Frank; Rudolph, Matthias; An, Qingzhi; Vaynzof, Yana; Hashmi, A. Stephen K. (Chemistry - a European journal, 2018)
A domino sequence, involving a phosphinoauration and a gold-catalyzed 6-endo-dig cyclization step, was developed. Starting from modular and simple-to-prepare phosphadiynes, π-extended phosphoniumfluorenes were synthesized. The mechanistic proposal was supported by kinetic measurements and by the trapping of key intermediates. These led to important conclusions for the gold-catalyzed hydroarylation mechanism. Cyclic voltammetry (CV) and UV/Vis spectroscopy measurements indicated interesting properties for materials science. The phosphoniumfluorene structure was tested as a hole-blocking layer in perovskite solar cells of inverted architecture. Devices with the phosphoniumfluorene exhibited an efficiency of 14.2 %, which was much higher than that of devices without (10.7 %).
Gesehen am 29.08.2018